2018
DOI: 10.1093/oso/9780190901349.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Law and Economics

Abstract: In the past few decades, economic analysis of law has been challenged by a growing body of experimental and empirical studies that attest to prevalent and systematic deviations from the assumptions of economic rationality. While the findings on bounded rationality and heuristics and biases were initially perceived as antithetical to standard economic and legal-economic analysis, over time they have been largely integrated into mainstream economic analysis, including economic analysis of law. Moreover, the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(32 citation statements)
references
References 0 publications
0
25
0
7
Order By: Relevance
“…54 In general, how findings from behavioral and experimental research -primarily tested in the context of individual decision making -unfold within groups greatly depends on a wide array of factors: group characteristics, decision-making procedures, the object of decision, and the decision task, 55 while furthermore taking into account that PIL offers many instances of advice taking, which differs from group decision making in subtle ways. 56 However, it has been shown that groups could be more vulnerable to framing effects than individuals. 57 Groups may amplify framing effects because of the high likelihood for initial framing effects at the individual level to interact, in potentially destructive ways, with processes of social influence.…”
Section: Applications In Public International Lawmentioning
confidence: 99%
“…54 In general, how findings from behavioral and experimental research -primarily tested in the context of individual decision making -unfold within groups greatly depends on a wide array of factors: group characteristics, decision-making procedures, the object of decision, and the decision task, 55 while furthermore taking into account that PIL offers many instances of advice taking, which differs from group decision making in subtle ways. 56 However, it has been shown that groups could be more vulnerable to framing effects than individuals. 57 Groups may amplify framing effects because of the high likelihood for initial framing effects at the individual level to interact, in potentially destructive ways, with processes of social influence.…”
Section: Applications In Public International Lawmentioning
confidence: 99%
“…The reference point is also influenced by status of other people. 47 In the domain of gains, people exhibit risk aversion, whereas they are risk seeking in the domain of losses.…”
Section: Intervening: Bounded Rationalitymentioning
confidence: 99%
“…The reference point is also influenced by the status of other people. 29 In the domain of gains, people exhibit risk aversion, whereas they are risk-seeking in the domain of losses.…”
Section: Towards Postnationalism and Multilateralisation: Coordinatmentioning
confidence: 99%